PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA KELAS IV SD NEGERI 1 SONOKULON TODANAN BLORA - Citra Ardela; Ervina Eka; Kiswoyo (STKIP Subang, 2023)
The background that drives this research is that based on observations, students' critical thinking abilities at SD Negeri 1 Sonokulon Todanan Blora, especially in class IV students, are still very low. Based on initial observations made at SD Negeri 1 Sonokulon Todanan Blora, the following problems were encountered: (1) there were still students who were unable to complete assignments. (2) there are still students who cannot explain further the purpose of learning. (3) there are still students who cannot grasp the essence of learning. One learning model that can be used to overcome problems related to students' low critical thinking abilities is the discovery learning model. The purpose of this research is to determine the critical thinking abilities of Class IV students at SD Negeri 1 Sonokulon Todanan Blora, to determine the influence of the Discovery Learning learning model on students' critical thinking abilities, to determine the increase in learning outcomes for students of Class IV at SD Negeri 1 Sonokulon Todanan Blora after being taught with the discovery learning model. This type of research is a quasi-experimental (quasi experimental) because the actual variables cannot be controlled or manipulated perfectly. The research design used was a one group pretest-posttest design, this research was carried out twice on a group of subjects, namely before treatment or also called pretest and after treatment or posttest. The results of this research are that students' critical thinking abilities before being taught using the discovery learning model received an average score of 55.28. then after being taught using the discovery learning model the average student's critical thinking ability was 81.25, the discovery learning learning model had an effect on students' critical thinking ability, the statistical results of the t test obtained a Sig (2-tailed) value of 0.000 < 0.05, or t -count 21.736 > t-table 1.69913, after being taught using the discovery learning model most of the students experienced a high increase in critical thinking skills, where based on the N-Gain calculation of 30 students, there were 16 (53.3%) students who experienced an increase high critical thinking ability, there were 14 (46.7%) students who experienced a moderate increase in critical thinking ability and none (0%) students experienced a low increase in critical thinking ability